Research on technological innovation decision-making considering government subsidies and corporate reputation - Yu Kang; Zhe Huang (PLoS ONE, 2025)
Aiming at the information asymmetry between pharmaceutical enterprises’ technological innovation decisions and government subsidy strategy, this paper establishes a differential game model consisting of the government and a single pharmaceutical company, proposes three different government subsidy strategies, and obtains an equilibrium solution with the help of the Hamilton-Jacobi-Bellman equation, taking into consideration of the transmission effect of the enterprise’s reputation. First, the innovation decisions of pharmaceutical firms without government subsidies are analysed, and based on this, the optimal strategies with government subsidies for non-cooperative pacts and cooperation between the government and enterprises are analysed separately. In addition, the effects of different subsidy strategies on the government’s investment efficiency, corporate reputation, and the choice of corporate innovation strategies are compared, and the results are verified by numerical analysis. Finally, based on the results of the study, references and suggestions are provided for the formulation of government subsidy policies as well as corporate innovation decisions. The results show that: government subsidies can effectively stimulate the innovation ability of pharmaceutical enterprises and improve their reputation; the more sensitive an enterprise’s reputation is to the coefficient of technological innovation, the more it can improve the enterprise’s innovation level; and the coordination contract of government-enterprise cooperation can realize the Pareto improvement of the benefits of the government and enterprises.